After the monkey trial: evangelical scientists and a new creationism - Rios, Christopher M. (Fordham Univ. Press, 2014)
Introduction -- Ebb and flow: Evangelicals and evolution, 1860s to 1940s -- A society for the correlation of science and the Bible: the American Scientific Afflilation, 1940s to 1965 -- Unexpected resistance: the Research Scientists' Christian Fellowship, 1940s to 1965 -- An increasingly powerful movement: modern creationism to the 1980s -- Against the tide: the American Scientific Afflilation, 1965 to 1985 -- A new apologetic: the Research Scientists' Christian Fellowship, 1965 to 1985 -- Conclusion